The influence of Gender and Self-Actualization on Student Achievement Motivation - Mustika, Ika (International Conference on Sustainable Health Promotion, 2024)
The process of self-actualization plays an important role in the learning process in order to achieve the desired goals, one of which is the achievement of achievement in learning. Achievement motivation is a factor that affects student achievement and success in the academic field in students. This study aims to determine the effect of gender and self-actualization on student achievement motivation. This research is an analytic observational study with a cross-sectional approach. The research was conducted on 159 students of UIN Sunan Ampel Surabaya. Data collection was carried out using google forms containing questions related to respondent characteristics, self-actualization and achievement motivation. The results of data collection were analyzed using multiple linear regression analysis with a 5% confidence level. The results showed that there was an influence between gender and self-actualization with student achievement motivation with a significance value of 0.000 <0.05. However, separately, it was found that gender did not significantly affect achievement motivation, while self-actualization had a significant effect on student achievement motivation